Institutional frameworks for the governance of hydropower resources in Indonesia: policy implications for sustainable rural development - Suswantoro, Endro; Nurrochmat, Dodik Ridho; Hidayat, Aceng; Sjaf, Sofyan (Frontiers in Environmental Science, 2026)
IntroductionThis study examines the institutional framework of economic governance for hydropower resources in Indonesia, focusing on interactions between national and subnational governance structures.MethodsData were drawn from national and regional policy documents on hydropower, renewable energy, and natural resource management; organizational structures and actor roles across government, private, and community stakeholders; meeting minutes, cooperation agreements, and institutional performance reports. These were complemented by in-depth interviews and focus group discussions with government officials, hydropower operators, community leaders, and civil society organizations. The Institutional Analysis and Development (IAD) framework and content analysis were used to map action arenas, actor networks, and rules-in-use.ResultsFindings reveal a multi-layered institutional configuration with overlapping mandates, fragmented coordination, and weak cross-sectoral integration. Although formal frameworks prescribe mechanisms for resource allocation, revenue distribution, and environmental safeguards, implementation is constrained by limited stakeholder engagement and weak enforcement.DiscussionThe institutional mapping provides a basis to strengthen coordination mechanisms, clarify actor mandates, and enhance participatory governance to achieve more coherent and equitable hydropower resource management in Indonesia.